Usability Study of Virtual Reality Media on the Theme Im Krankenhaus in A2-Level German Language Learning at Universitas Negeri Malang - Amanda Putri Kurnia; Iwa Sobara; Ikmal Trianto (Nexus Publishing, 2026)
This study examines the usability of a Virtual Reality (VR)-based learning medium entitled Im Krankenhaus in A2-level German language learning at Universitas Negeri Malang. The study responds to the need for contextual and immersive learning media that support situational communication, particularly in healthcare-related contexts. A descriptive quantitative approach was employed involving 20 students from the German Language Education Study Program. Data were collected using the System Usability Scale (SUS). The results showed that the Im Krankenhaus VR medium achieved a mean SUS score of 70.5, placing it in the acceptable category with a Grade B classification. This indicates that the medium demonstrates a good level of usability and is suitable for German language learning. Item-level analysis revealed strong learnability, as participants perceived the system as easy to use and easy to learn. Furthermore, participants’ willingness to reuse the VR medium reflected a positive level of satisfaction, indicating a favorable user experience and increased confidence during interaction with the system. However, some participants still required assistance and an adaptation period during initial use. The novelty of this study lies in its focus on the usability of VR-based media in German language learning within a healthcare communication context. The findings suggest that VR has considerable potential as an immersive and contextual learning medium, particularly when accompanied by adequate user orientation and guidance.